2013
DOI: 10.3386/w19426
|View full text |Cite
|
Sign up to set email alerts
|

Envirodevonomics: A Research Agenda for a Young Field

Abstract: Environmental quality in many developing countries is poor and generates substantial health and productivity costs. However, existing measures of willingness to pay for environmental quality improvements indicate low valuations by affected households. This paper argues that this seeming paradox is the central puzzle at the intersection of environmental and development economics: Given poor environmental quality and high health burdens in developing countries, why is WTP so low? We develop a conceptual framewor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 109 publications
0
5
0
Order By: Relevance
“…While all of these countries still have elements of the archetypal developing economy, they are all increasingly urbanized, and are all increasingly experiencing the challenges of rapid industrialization when environmental regulations are weak. The central question posed in the paper that originally stimulated this review (Greenstone and Jack, 2013) is most relevant in Beijing, Delhi, Sao Paulo, Johannesburg or Mexico City, where air, soil and water pollution are major issues.…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…While all of these countries still have elements of the archetypal developing economy, they are all increasingly urbanized, and are all increasingly experiencing the challenges of rapid industrialization when environmental regulations are weak. The central question posed in the paper that originally stimulated this review (Greenstone and Jack, 2013) is most relevant in Beijing, Delhi, Sao Paulo, Johannesburg or Mexico City, where air, soil and water pollution are major issues.…”
Section: Future Directionsmentioning
confidence: 99%
“…They claim that the new field might be organized around a central question: why is environmental quality so poor in developing countries? They then offer, as candidate answers to their question: the high marginal utility of consumption at low income levels and the high marginal cost of environmental quality improvement, together with market and policy failures (Greenstone and Jack 2013). Since they cite almost none of the existing literature on these topics, it prompted me to consider how well their perceptions might map to the evolution of the field as it has developed over the last two decades.…”
Section: Introductionmentioning
confidence: 99%
“…Air quality affects a person's utility of public good. An individual's willingness to pay (WTP) taxes for the betterment of air quality can serve as the main factor when an exchange between economic development and environmental regulations takes place ( 2 ). In this respect, since 1990s, there has been a growing trend toward studying well-being (or “happiness research” or “quality of life research”) theoretically or empirically ( 3 – 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Greenstone and Jack (2013) suggest that few studies have attempted to develop revealed preference estimates of WTP for environmental quality in developing countries, despite the fact that recent pollution concentrations in these countries are far above those ever recorded in the US. The extrapolation of WTP estimators from studies in developed countries is unlikely to be valid because pollution and income levels are substantially di↵erent among developed and developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…Optimal environmental regulation depends on the extent to which individuals value air quality improvements-that is, their willingness to pay (WTP) for clean air (Greenstone and Jack, 2013). If WTP for clean air is low, the current level of air pollution can be optimal because social planners prioritize economic growth over environmental regulation.…”
Section: Introductionmentioning
confidence: 99%